Knee injury prevention in alpine skiing. A technological paradigm shift towards a mechatronic ski binding. Issue 10 (October 2021) - Hermann, Aljoscha; Senner, Veit
Abstract: Background: Skiing can be beneficial for the sense of delight and wellbeing. Nonetheless, the risk of injury should not be ignored. The traditional ski binding, working solely on a mechanical principle, performs well with regards to a prevention of mid-shaft tibia fracture. However, with respect to knee injuries, it is not able to provide protection. Future concepts, such as mechatronic binding designs have the potential to decrease knee injuries that traditional bindings cannot prevent. In addition to mechanical loads, this kind of binding design uses additional parameters, e.g. knee kinematics and the skier's muscle state, to control the binding release. Methods: This paper provides a review about our knowledge of injury mechanisms in recreational alpine skiing and previous work regarding mechatronic ski binding concepts. Also, our own biomechanical approach towards a mechatronic ski binding is described. Four input variables for an algorithm are discussed with respect to existing sensor solutions and designs of our own. A concept for an algorithm, based on our current knowledge in injury mechanisms is presented. Conclusions: Though first designs were described in the 80s, for decades the idea of a mechatronic ski binding was not further pursued by research. Technological improvements in the field of micro-electronics and wearable sensors, as well as decreasing costs of these devices, make a mechatronic concept feasible. Main challenge is still the missing knowledge about injury mechanisms in alpine skiing and hence the quantification of the influence of possible input variables for the mechatronic system on those injuries.